2011
DOI: 10.1016/j.ejpain.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Survey of undergraduate pain curricula for healthcare professionals in the United Kingdom

Abstract: The prevalence and burden of pain has long been reported as problematic. Comprehensive pain education in undergraduate programmes is essential for developing knowledgeable, skilled and effective healthcare professionals. This cross-sectional survey describes the nature, content and learning strategies for pain curricula in undergraduate healthcare programmes in major universities in the United Kingdom (UK). Document analysis also highlighted gaps in pain-related standards from professional regulators and a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
182
0
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(203 citation statements)
references
References 40 publications
(52 reference statements)
5
182
0
16
Order By: Relevance
“…A recent British report indicated that pain education represents less than 1% of the curricula in health care professions. [53] Several other investigators found that in current undergraduate nursing curricula, there is limited information on pain assessment and management available to undergraduate students. [28,29,35,54,55] Twycross [56] found that students receive only two class hours of pain education with more focus on pharmacological treatment.…”
Section: Bmentioning
confidence: 99%
“…A recent British report indicated that pain education represents less than 1% of the curricula in health care professions. [53] Several other investigators found that in current undergraduate nursing curricula, there is limited information on pain assessment and management available to undergraduate students. [28,29,35,54,55] Twycross [56] found that students receive only two class hours of pain education with more focus on pharmacological treatment.…”
Section: Bmentioning
confidence: 99%
“…It has been found that, on average, physiotherapy students have a greater amount of pain education compared to other health disciplines (Briggs, Carrl, andWhittakerl 2011, WattWatson et al 2009). These studies have not considered the quality of teaching though, with Etherton and Waterfield (2015) finding that physiotherapy students have felt unprepared to manage pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although pain education has been identified as a strategy to improve ineffective pain management practices [6], recent evidence demonstrates the continuing lack of pain content in health science curricula, particularly for students in their first professional program (prelicensure/undergraduate/entry-to-practice) [7][8][9] IASP has also recognized the importance of collaboration and interprofessional education. Building on the successful uniprofessional curricula, it has recently developed an Interprofessional Pain Curriculum Outline to be available online to members and the wider community.…”
Section: Lack Of Pain Content In Prelicensure (Undergraduate) Curriculamentioning
confidence: 99%
“…An important question to ask is the degree to which pain content is a component of required curricula in health science faculties. Two recent cross-sectional studies underline a lack of attention to this complex healthcare issue in health science curricula [7,8]. In both Canada and the UK, the content emphasis was considerably less for pain assessment, which is essential to management, compared with neurophysiology and management strategies such as pharmacology.…”
Section: Lack Of Pain Content In Prelicensure (Undergraduate) Curriculamentioning
confidence: 99%